Gold-Polymer Nanocomposites for Future Therapeutic and Tissue Engineering Applications - Panangattukara Prabhakaran Praveen Kumar; Dong-Kwon Lim (MDPI AG, 2021)
Gold nanoparticles (AuNPs) have been extensively investigated for their use in various biomedical applications. Owing to their biocompatibility, simple surface modifications, and electrical and unique optical properties, AuNPs are considered promising nanomaterials for use in in vitro disease diagnosis, in vivo imaging, drug delivery, and tissue engineering applications. The functionality of AuNPs may be further expanded by producing hybrid nanocomposites with polymers that provide additional functions, responsiveness, and improved biocompatibility. Polymers may deliver large quantities of drugs or genes in therapeutic applications. A polymer alters the surface charges of AuNPs to improve or modulate cellular uptake efficiency and their biodistribution in the body. Furthermore, designing the functionality of nanocomposites to respond to an endo- or exogenous stimulus, such as pH, enzymes, or light, may facilitate the development of novel therapeutic applications. In this review, we focus on the recent progress in the use of AuNPs and Au-polymer nanocomposites in therapeutic applications such as drug or gene delivery, photothermal therapy, and tissue engineering.